Disrupted Gamma Synchrony after Mild Traumatic Brain Injury and Its Correlation with White Matter Abnormality - Wang, Chao; Costanzo, Michelle E.; Rapp, Paul E.; Darmon, David; Nathan, Dominic E.; Bashirelahi, Kylee; Pham, Dzung L.; Roy, Michael J.; Keyser, David O. (Frontiers in Neurology, 2017)
Mild traumatic brain injury (mTBI) has been firmly associated with disrupted white matter integrity due to induced white matter damage and degeneration. However, comparatively less is known about the changes of the intrinsic functional connectivity mediated via neural synchronization in the brain after mTBI. Moreover, despite the presumed link between structural and functional connectivity, no existing studies in mTBI have demonstrated clear association between the structural abnormality of white matter axons and the disruption of neural synchronization. To investigate these questions, we recorded resting state EEG and diffusion tensor imaging (DTI) from a cohort of military service members. A newly developed synchronization measure, the weighted phase lag index (WPLI) was applied on the EEG data for estimating neural synchronization. Fractional anisotropy (FA) was computed from the DTI data for estimating white matter integrity. Fifteen service members with a history of mTBI within the past 3 years were compared to twenty-two demographically similar controls who reported no history of head injury. We observed that synchronization at low-gamma frequency band (25-40 Hz) across scalp regions was significantly decreased in mTBI cases compared with controls. The synchronization in theta (4-7 Hz), alpha (8-13 Hz), and beta (15-23 Hz) frequency bands were not significantly different between the two groups. In addition, we found that across mTBI subjects, the disrupted synchronization at low-gamma frequency was significantly correlated with the white matter integrity of the inferior cerebellar peduncle, which was also significantly reduced in the mTBI group. These findings demonstrate an initial correlation between the impairment of white matter integrity and alterations in EEG synchronization in the brain after mTBI. The results also suggest that disruption of intrinsic neural synchronization at low-gamma frequency may be a characteristic functional pathology following mTBI and may prove useful for developing better methods of diagnosis and treatment.